Modulation of gallbladder contraction by pirenzepine in humans - (:unkn) unknown (My University, 1995)
OBJECTIVES: The mechanism(s) by which cholinergic innervation modulates gallbladder contraction are not fully understood. To elucidate the role of muscarinic M1 receptors in the mediation of gallbladder contraction, we investigated gallbladder volume reduction, plasma cholecystokinin (CCK), and pancreatic polypeptide (PP) responses in humans during cephalic and intestinal phases of a meal under M1 muscarinic receptor blockade with pirenzepine. METHODS: In eight healthy subjects, intraduodenal meal- and in seven subjects, sham feeding-induced gallbladder volume reduction was measured by real-time ultrasonography during saline or pirenzepine administration. Plasma CCK and PP were measured by radioimmunoassay. RESULTS: Pirenzepine partially inhibited gallbladder volume reduction in response to an intraduodenal fatty meal. The integrated gallbladder volume reduction over 120 min was 4462 +/- 445%.min compared with 6879 +/- 279%.min in the saline control group (p < 0.01). Integrated plasma CCK and PP responses were unchanged in the presence of pirenzepine. Pirenzepine abolished sham feeding-induced gallbladder contraction and plasma PP response. Sham feeding with either isotonic saline or pirenzepine infusion did not modify fasting plasma CCK levels. CONCLUSION: M1 muscarinic receptors play an important role in the intestinal and cephalic phases of gallbladder contraction. Plasma CCK response to intraduodenal meal is not influenced by M1 muscarinic receptor blockade with pirenzepine.
Keywords: Adult; Humans; Ultrasonography; Male; Pirenzepine; Cholecystokinin; Receptors, Muscarinic; Gallbladder; Radioimmunoassay; Food; Gallbladder Emptying; Pancreatic Polypeptide